2008
DOI: 10.1007/978-3-540-85990-1_61
|View full text |Cite
|
Sign up to set email alerts
|

MRI Compatibility of Robot Actuation Techniques – A Comparative Study

Abstract: Abstract. This paper reports an experimental evaluation of the following three different MRI-compatible actuators: a Shinsei ultrasonic motor, a Nanomotion ultrasonic motor and a pneumatic cylinder actuator. We report the results of a study comparing the effect of these actuators on the signal to noise ratio (SNR) of MRI images under a variety of experimental conditions. Evaluation was performed with the controller inside and outside the scanner room and with both 1.5T and 3T MRI scanners. Pneumatic cylinders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 13 publications
1
58
2
Order By: Relevance
“…Our previous studies in MR compatible actuation demonstrated that non-magnetic piezo-ceramic motors provide good MR compatibility, relatively compact size, and simplicity of operation [24], [25]. Recent work by Wang et al has shown that with proper driving signal conditioning, it is possible to operate certain classes of rotary piezo-electric motors during MR scans without significant reduction to the MRI SNR [26].…”
Section: Actuation and Feedback Controlmentioning
confidence: 97%
“…Our previous studies in MR compatible actuation demonstrated that non-magnetic piezo-ceramic motors provide good MR compatibility, relatively compact size, and simplicity of operation [24], [25]. Recent work by Wang et al has shown that with proper driving signal conditioning, it is possible to operate certain classes of rotary piezo-electric motors during MR scans without significant reduction to the MRI SNR [26].…”
Section: Actuation and Feedback Controlmentioning
confidence: 97%
“…This implies that it is impossible to generate the gradients in (3) without also generating concomitant gradients. As a result, the complete field B g is given by [15]: (4) where g⃗ is as given in (3), x⃗ is the position vector from the origin of the XYZ frame, ẑ is the unit vector along the z-axis and G c is a matrix containing the concomitant gradients and is given by: (5) Differentiating the x and y components of (4) with respect to the z coordinate yields: (6) Hence, the gradients of (2) are equal to the imaging gradients of (3) and, furthermore, all three are linearly independent. Thus, they are capable of inducing 3 degree of freedom (DOF) motion in a ferromagnetic body.…”
Section: Background Theorymentioning
confidence: 99%
“…1Nm) and speed (rated 100rpm) ratings are easily sufficient for the low friction and low reduction characteristics of the robot. As studies have shown that these motors are capable of affecting an MRI image when powered inside the tunnel [8], it was decided to house them in a separate container placed on the scanner or MRI bed, at the patient's feet (see Figure 1, right). They are connected to the robot by 1.5m long cables and housing, ensuring that they are never inside the tunnel.…”
Section: Robot Descriptionmentioning
confidence: 99%
“…The SNR was measured in exactly the same manner as described in [1] and [8], using a phantom bottle in a Philips Achieva 3.0T MRI scanner. BTFE 1 and THRIVE 2 sequences, typically used during IR, were taken.…”
Section: Ct and Mri Compatibilitymentioning
confidence: 99%